Wernicke's encephalopathy after acute pancreatitis with upper gastrointestinal obstruction: A case report and literature review - Wang, Zongding; Zhang, Lei; Deng, Xingzhen; Peng, Zili; Liang, Shaoyong (Frontiers in Neurology, 2023)
A 42-year-old female was admitted with upper abdominal pain. Imaging studies and laboratory tests were performed to consider acute lipogenic pancreatitis. After symptomatic treatment, her abdominal pain was significantly relieved. However, the patient was accompanied by upper gastrointestinal obstruction, which was gradually relieved after long-term fasting, gastrointestinal decompression, and fluid rehydration. The patient developed dizziness and ataxia, which worsened. Cranial magnetic resonance imaging (MRI) indicated patchy abnormal signal shadows in the bilateral thalami and dorsal brainstem and suggested metabolic encephalopathy. Wernicke's encephalopathy (WE) was the initial diagnosis of suspicion, adequate vitamin B1 was immediately replenished until the complete resolution of symptoms, and the patient made a rapid and dramatic recovery.